The inhibition of ORMDL3 prevents Alzheimer's disease through ferroptosis by PERK/ATF4/HSPA5 pathway - Yankun Shao; Yilin Xu; Huang Di; Xinxiu Shi; Yingying Wang; Hongyu Liu; Lina Song (IET Nanobiotechnology)
Abstract Alzheimer's disease (AD) is a neurodegenerative disease with high incidence and widespread attention. There is currently no clear clarification of the pathogenesis. However, ORMDL3 causes ferroptosis in AD, and the potential mechanisms remain unclear. So, this study explore the function of ORMDL3 on ferroptosis in AD and its potential regulatory mechanisms. APPswe/PS1dE9 mice and C57BL/6 mice were induced into the mice model. The murine microglial BV‐2 cells also were induced into the vitro model. In serum samples of AD patients, ORMDL3 mRNA expression levels were upregulated. The serum ORMDL3 levels expression was positively related to the ADL score or MoCA score in AD patients. The serum ORMDL3 expression level was positively related to MMSE score or Hcy levels in AD patients. The mRNA expression of ORMDL3 in the hippocampal tissue of the mice model of AD was upregulated at one, four and eight months. The protein expression of ORMDL3 was upregulated in the mice model of AD. ORMDL3 promoted Alzheimer's disease, and increased oxidative response and ferroptosis in a model of AD. PERK/ATF4/HSPA5 pathway is one important signal pathway for the effects of ORMDL3 in a model of AD. Collectively, these data suggested that ORMDL3 promoted oxidative response and ferroptosis in a model of AD by the PERK/ATF4/HSPA5 pathway, which might be a novel target spot mechanism of ferroptosis in AD and may serve as a regulator of AD‐induced ferroptosis.